KUALITAS SPERMATOZOA ASAL CAPUT, CORPUS, DAN CAUDA EPIDIDIMIS PADA KERBAU RAWA (Bubalus bubalis carabenensis) - Muhammad Riyadhi; Akbar Budiansa; Muhammad Rizal (Universitas Halu Oleo, 2016)
The purpose of this research was evaluate the quality of spermatozoa concentration in the caput, corpus and cauda of the swamp buffalo epididymis (Bubalus bubalis carabanensis). Method of this research was to exploration to 13 epididymides of eight swamp buffaloes were obtained from Banjar and Banjarmasin slaughterhouses,evaluated the quality of spermatozoa in caput, corpus and cauda of epididymis. Quality of collected-spermatozoa including spermatozoa motility, percentage of live spermatozoa, spermatozoa concentration and percentage of abnormality. Result of this study showed that mean of each of caput spermatozoa motility, percentage of live spermatozoa, spermatozoa concentration and percentage of abnormality; 0%, 45.43% (31.87–72%), 189,62 x106 (40–480 x106) and 56.16 %(44.34–66.53%), corpus ;2.77% (1–9%), 58.73% (45.14 –76%), 152.31 x106 (45 – 345x106), and 47.61 %(23.92 – 60.15%), cauda;53.46% (20 – 70%), 74.32 % (56.68 – 83%), 1,459.62 x106 (825 – 2,340x106), and 34.60%(15.89 –50.04%). In conclusion, spermatozoaofcaudaepididymis could be used in artificial insemination program.Keywords: Spermatozoa, epididymis, swamp buffalo.